Postmarketing Research for Opioid Abuse-Deterrent Formulations: A Narrative Review - Webster L; Gudin J; Green JL; Argoff CE (Journal of Pain Research)
Lynn Webster,1 Jeff Gudin,2 Jody L Green,3 Charles E Argoff4 1Dr. Vince Clinical Research, Overland Park, KS, USA; 2University of Miami, Miller School of Medicine, Miami, FL, USA; 3Inflexxion, a Division of Uprise Health, Irvine, CA, USA; 4Department of Neurology, Albany Medical College, Albany, NY, USACorrespondence: Lynn Webster, Executive Vice President, Scientific Affairs, Dr. Vince Clinical Research, 7401 W 91st St, Overland Park, KS, 66212, USA, Tel +1913-333-3000, Email LRWebsterMD@gmail.comAbstract: Although prescription opioids may be necessary to manage severe and persistent pain, many factors including concern for opioid abuse and misuse have led to restricted availability of these analgesics. Opioid abuse-deterrent formulations (ADFs) were developed to enhance resistance to tampering yet retain analgesic efficacy. US Food and Drug Administration (FDA) approval for the ADF designation is based on prespecified preclinical (category 1), pharmacokinetic (category 2), and/or clinical (category 3) evidence demonstrating abuse-deterrent properties. Currently, 4 opioid formulations carry the ADF designation: XTAMPZA® ER (oxycodone), OXYCONTIN® (oxycodone hydrochloride), HYSINGLA™ ER (hydrocodone bitartrate), and ROXYBOND™ (oxycodone hydrochloride). The FDA requires that ADFs undergo postapproval evaluation to assess their impact on meaningful reductions in abuse, misuse, and related clinical outcomes. An additional designation is available based on FDA assessment of these postmarket studies (category 4). However, none of the 4 opioid ADFs have yet attained this additional category 4 labeling. The impact of opioid ADFs on abuse, misuse, and related clinical outcomes is unclear. The objectives of this narrative review are 1) to describe the benefits of and need for ADFs; 2) to provide an overview of the FDA guidance for ADFs, with a focus on category 4 postmarketing requirements; and 3) to summarize select postmarketing studies of the ADF prescription opioids currently available in the US. We identified key postmarketing publications for these ADFs via PubMed searches and investigation of literature cited in relevant publications. Three opioid ADFs (XTAMPZA ER, OXYCONTIN, and HYSINGLA ER) currently report postmarketing research, generally demonstrating reduced nonoral abuse or misuse compared with non-ADFs or other ADFs. Of note, XTAMPZA ER has shown sustained lower levels of nonoral abuse or misuse compared with other ADFs, despite a substantial increase in dispensed prescriptions since its launch in 2016. Additional postmarketing research is needed, especially for HYSINGLA ER and ROXYBOND.Keywords: ADF categories, oxycodone, hydrocodone, postmarketing research